Risk and promise: an 11-year, single-center retrospective study of severe acute GVHD in pediatric patients undergoing allogeneic HSCT for nonmalignant diseases - Zaidman, Irina; Even-Or, Ehud; Aharoni, Elroee; Averbuch, Dina; Dinur-Schejter, Yael; NaserEddin, Adeeb; Slae, Mordechai; Shadur, Bella; Stepensky, Polina (Frontiers in Pediatrics, 2023)
Background Hematopoietic stem cell transplantation (HSCT) is the only curative option for many nonmalignant hematopoietic-derived diseases in pediatric patients. Survival after HSCT has improved in recent years and resulted in a 90% survival rate and cure in some nonmalignant diseases. Graft-vs.-host disease (GVHD) remains a frequent and major complication of HSCT, and a leading cause of morbidity and mortality. Prognosis of patients with high-grade GVHD is dismal, with survival rates varying from 25% in the adult population to 55% in pediatric patients. Methods The main aim of this study is to evaluate the incidence, risk factors, and outcome of severe acute GVHD (AGVHD) in pediatric patients with nonmalignant diseases, following allogeneic HSCT. Clinical and transplant data were retrospectively collected for all pediatric patients who underwent allogeneic HSCT for nonmalignant diseases at the Hadassah Medical Center between 2008 and 2019. Patients who developed severe AGVHD were compared with those who did not. Results A total of 247 children with nonmalignant diseases underwent 266 allogeneic HSCTs at Hadassah University Hospital over an 11-year period. Seventy-two patients (29.1%) developed AGVHD, 35 of them (14.1%) severe AGVHD (grade 3–4). Significant risk factors for developing severe AGVHD were unrelated donor (p < 0.001), mismatch donor (p < 0.001), and the use of peripheral blood stem cells (PBSCs) (p < 0.001). Survival rates of pediatric patients with severe AGVHD was 71.4%, compared with 91.9% among those with mild (grade 1–2) AGVHD and 83.4% among patients without AGVHD (p = 0.067). Conclusions These results demonstrate a high survival rate in pediatric patients with nonmalignant diseases despite severe GVHD. Significant mortality risk factors found in these patients were the source of donor PBSC (p = 0.016) and poor response to steroid treatment (p = 0.007).